2009
DOI: 10.1007/s00464-009-0742-6
|View full text |Cite
|
Sign up to set email alerts
|

Increased vascular endothelial growth factor transcription in residual hepatocellular carcinoma after open versus laparoscopic hepatectomy in a small animal model

Abstract: Laparoscopic hepatic resection produces decreased VEGF mRNA expression in residual hepatoma cells compared with open resection. Decreased stimulation of angiogenesis promoters in the tumor microenvironment after minimally invasive liver resection may contribute to a lower residual disease burden and ultimately lead to a lower recurrence rate.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
5
0
1

Year Published

2010
2010
2014
2014

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 39 publications
2
5
0
1
Order By: Relevance
“…Our experimental research revealed that palliative resection is followed by acceleration of metastatic processes in the lungs. The increased pulmonary metastatic nodules were found in the palliative resection group (14.3 ± 4.7) compared to controls (8.7 ± 3.6), which may be partially due to breakdown of tumor MMP2/TIMP2 balance and in situ up-regulation of VEGF that was consistent with a recent report that confirmed increased VEGF transcription in residual HCC after hepatectomy in a small animal model [25]. …”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…Our experimental research revealed that palliative resection is followed by acceleration of metastatic processes in the lungs. The increased pulmonary metastatic nodules were found in the palliative resection group (14.3 ± 4.7) compared to controls (8.7 ± 3.6), which may be partially due to breakdown of tumor MMP2/TIMP2 balance and in situ up-regulation of VEGF that was consistent with a recent report that confirmed increased VEGF transcription in residual HCC after hepatectomy in a small animal model [25]. …”
Section: Discussionsupporting
confidence: 89%
“…VEGF, a potent stimulator of tumor angiogenesis, is believed to have a major role in HCC angiogenesis, growth, and metastasis. In this study, we found palliative liver resection elevated tumor VEGF levels markedly, in accordance with the literature [25]. The alteration of endostatin (a potent angiogenesis inhibitor) and MT1-MMP (an activator of MMP2) was minor, which indicated that elevated tumor VEGF and increased MMP2 activity were not directly due to endostatin and MT1-MMP, whose detailed molecular mechanism remains to be elucidated.…”
Section: Discussionsupporting
confidence: 89%
“…One can expect improved oncologic outcomes after application of laparoscopic techniques due to less invasive intervention and therefore less stress response, less immunologic alterations and minor activation of regenerative growth which promotes tumour recurrence (106)(107). However these theoretical and experimental premises have to be confirmed in clinical settings.…”
Section: Oncologic Outcomesmentioning
confidence: 99%
“…Clinically established nontargeted SonoVue microbubbles served as a control. As an animal model for liver carcinogenesis, we used hepatocyte-specific NEMO knock-out mice that develop chronic hepatitis after birth and show disease progression to dysplasia and hepatocellular carcinomas upregulation of proangiogenic receptors (eg, VEGFR2) is observed (26)(27)(28). Detection of this enhanced receptor expression might be an alternative diagnostic strategy for detection of liver dysplasia or well-differentiated hepatocellular carcinomas.…”
Section: Molecular Imaging: Targeted Us Microbubbles For Liver Dysplasiamentioning
confidence: 99%